Enhancing Relationality through Poetic Engagement with PhoneMe: Transmodal Contexts and Interpretive Agency - Ahn, Claire; Balyasnikova, Natalia; Horst, Rachel; James, Kedrick; Morales, Esteban; Takeda, Yuya; Yung, Effiam (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2023)
This article explores the role of literary user preference and experience of contextualizing information in the interpretive responses to poems on PhoneMe, a social media web-platform and mobile app for place-based spoken word poetry. 137 education students in three Canadian universities participated by completing a survey that asked them to choose one of three stylistically distinct poems and subsequently introduced multimodal contextual information about the poet and location inspiring the poem. Findings indicate a productive tension between the reader/user’s interpretive agency with typographic text and the increasing relationality imposed by indexical, transmodal information, thus helping to update Reader Response theory.